ANALISIS KETERAMPILAN BERPIKIR KRITIS SERTA KEMANDIRIAN BELAJAR SISWA SMA PADA MATERI HUKUM NEWTON - Sulviana, Sulviana; Pasaribu, Marungkil (Universitas Tadulako, 2021)
This study aims to identify the level of critical thinking skills of high school students in Newton's Law material. To determine the level of learning independence of high school students. To determine the relationship between student learning independence and critical thinking skills of class XI high school students on Newton's Law material. The subjects of this study consisted of 20 high school students of class XI. The data collection research instruments used were critical thinking essay tests, independent learning questionnaires and interviews. The essay test is a question of describing critical thinking skills in Newton's law material. The essay test consists of 5 items given to the research subject. Then, interviews were conducted with 6 respondents who were randomly selected. Based on the results of research and data analysis, it shows that the students 'critical thinking skills are in the sufficient category with an average presentation of 59%, while the students' learning independence is in the good category. Then based on the results of the analysis of the two variables using the Spearman rank test using SPSS, it was found that the two variables did not have a significant relationship. This is indicated by the r count value of 0.256 then compared with the r table value of 0.450. The correlation value is in the weak category.